0=9(k-(2/3))+33

Simple and best practice solution for 0=9(k-(2/3))+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=9(k-(2/3))+33 equation:


k in (-oo:+oo)

0 = 9*(k-(2/3))+33 // - 9*(k-(2/3))+33

0-(9*(k-(2/3)))-33 = 0

-9*(k-2/3)-33 = 0

-9*(k-2/3)-33 = 0

-9*k-27 = 0

-9*k-27 = 0

-9*k-27 = 0 // + 27

-9*k = 27 // : -9

k = 27/(-9)

k = -3

k = -3

See similar equations:

| 53=8c-3 | | y=32x+4 | | -3.2y-0.7y= | | -3(-21)=x | | x+17=x^2+25 | | 1/8/1/8 | | 1/3t=5/6 | | x^2-x=1.5 | | 7x+43=-6 | | 0.-3=-1 | | 4y-y+6=15 | | 36=b^2/5 | | -407y-2.3y= | | 2xy-7xy+4z-7z= | | 4z-7z= | | 2xy-7xy= | | 2x+y=95 | | 7x+54+2x=180 | | -4z-1z= | | 0.10x+0.05(6-x)=0.10(8) | | -10=-x/2+20 | | 25xy+13xy= | | t=-36t^2+ct+k | | x^2=9x+100 | | h=-36t^2+ct+k | | a^2+10ab-39b^2= | | x/5-(-3)=4 | | X/-9=13 | | 10x=96-6x | | X/3-5=25 | | -(4/5)+y=-(2/3) | | (x-1/4)(x+1/5)=0 |

Equations solver categories